Evaluation of selected heavy metal and selenium pollution in water and sediments of Lake Eğirdir (Isparta/Türkiye) using statistical analysis and pollution indices - Özçelik Şule; Tekin-Özan Selda (Oceanological and Hydrobiological Studies)
The purpose of this study is to assess heavy metal and selenium pollution in water and sediment of Lake Eğirdir using some indices. The water and sediments have the highest content of Fe. According to Water Quality Index (WQI) results, the lake water is in the good category, while the low pollution category depends on HPI and HEI values. The Enrichment Factor (EF) showed that the sediments contained very high, extremely high and significant levels of Pb, Cr, Cu, Mn, Ni and Fe. The Geoaccumulation Index (Igeo) revealed that Lake Eğirdir was not polluted with Cr, Cu, Fe, Mn, Mo, Ni and Zn. Based on the results of the Contamination Factor (CF), Cr, Cu, Fe, Mn, Mo, Ni and Zn were in the low contamination category. The results of The Pollution Load Index (PLI) for lake sediments indicated no contamination for all metals in all seasons. Sediment quality guidelines were used to determine the possible risk of heavy metal contamination of sediments, and the results show that Cd and Pb were at the minimal effect threshold (MET), while Cr, Cu, Ni and Zn were at the lowest effect levels (LEL). These results indicate that precautions should be taken to prevent an increase in metal pollution and reduce the existing pollution.